Functional Outcome of Bilateral Subthalamic Nucleus-Deep Brain Stimulation in Advanced Parkinson's Disease Patients: A Prospective Study - Tandra, Swetha (Ann Indian Acad Neurol, 2020)
BACKGROUND: Deep brain stimulation (DBS) is an accepted modality of treatment in patients with Parkinson's disease (PD). Although DBS was approved in advanced PD, it is being done in early PD as well. It was mainly developed to help the patients of PD to overcome the adverse motor effects associated with treatment and treatment failure. OBJECTIVE: The objective is to study the efficacy of subthalamic nucleus (STN)-DBS procedure in patients with PD. MATERIALS AND METHODS: This was a prospective, single-center, follow-up observational study using a direct, structured interview of 40 selected PD patients. Preoperative assessment using Unified PD Rating Scale-III (UPDRS-III), Montreal Cognitive Assessment (MOCA), and Parkinson's Disease Questionnaire-39 were done. All the patients underwent DBS. Postoperatively, similar assessment was done during follow-up period of 6 months. The results were analyzed using Student's t-test. RESULTS: The total score of UPDRS-III was reduced by 35% after STN-DBS intervention which was statistically significant (P < 0.05). STN-DBS intervention was successful in significantly reducing all UPDRS-III subscores but failed to reduce the scores in case of postural stability. MOCA scores of the patients were not found to be affected by STN-DBS intervention (P = 0.1466). Similar findings were also observed for MOCA subscores, but there was significant improvement of verbal fluency in all patients. Quality of life(QoL) improved significantly in all patients after STN-DBS intervention in all areas. Lower baseline UPDRS-III scores were found to enhance the QoL both in “off” and “on” state. However, prolonged disease duration and older age at PD onset were found to be hampering factors in the improvement of QoL. CONCLUSIONS: STN-DBS is a safe procedure and can be performed in all patients of PD who develop disabling motor fluctuations to improve their QoL irrespective early or advanced disease.